The Effect of Plants on Extensive Green Roofs in Urban Heat Island Mitigation Efforts in Humid Tropical Cities. Issue 1 (November 2021) - Irfandi,; Munir, Abdul; Muslimsyah,; Huda, Khairul
Abstract: One of the urban heat island mitigation strategies in reducing urban temperatures in tropical cities is the application of a green roof system. This study compares the reduction in temperature and heat flow rate provided by three types of plants on extensive green roofs (EGR). We demonstrated that a EGR constructed with three types of plants (ground cover, and shrubs) could result in a decrease in temperature relative to the normal roof (NR). The results showed that the base temperature of the EGR of the bush and ground cover was lower than the base temperature of the NR which was 10.2ºC on indoor air, 17.8ºC on the inside and 19.1ºC on the outside. The peak indoor temperature was over 50ºC for the NR prototype. In the model with pennisetum purpureum schamach as the EGR, the maximum temperature was 40.1ºC, while for portulaca grandiflora and tradescantia spathacea the peaks were 37.6ºC and 37.5ºC, respectively. This shows that plants with large leaf widths are able to reduce heat greater than plants with small leaf widths.